Uniwersalizm i regionalizm w socjologii - Ziółkowski, Janusz (Wydział Prawa i Administracji UAM, 1987)
Universalism in sociology has many dimensions. It denotes: 1) the search of cultural generalities, the universal model of culture which reflects the "human nature" and humanity, 2) the search of general, universal regularities in social •life and the formulation of strictly general sentences about those regularities (sociology as nomotetic science), 3) the spread of universal scientific standards in sociology, 4) the growing process of institutionalisation of sociology on a worldwide scale, 5) the worldwide perspective of researched problems, 6) the diffusion of ideas, the process of scientific communication by means of one or several "world" languages, 7) the development of the international system of information in sociology (in social sciences in general). Being universal science, sociology is not able to disengage itself from its cultural environment. Its cultural environment is, of course, a national community, but more often and to a greater degree a geo-cultural region becomes the one. The most characteristic feature of the development of sociology is its asymetric character. Sociology is practised first of all in Europe and in North America. The relations of intellectual dependence on the part of the rest the world appear, being the reflex of dependency in economical, technological or political spheres. The process of autochthonisation of sociology is an expression of protest against the said dependence. It consists in striving to establish one's own research and teaching institutions, in developing sociology in agreement with one's own systems of values and in formulating one's own paradigms and methods. Poor development of sociology on a national level induces to enter into cooperation on a regional scale. The regionalism and the emancipation movement with respect to the development of sociology appear in the Third World countries. Practising sociology becomes thus an intellectual undertaking encompassing the entire globe.
Universalism and Regionalism in Sociology